Soil Properties and Variation between Three Forest Types in Tropical Watershed Forest of Chini Lake, Peninsular Malaysia - Khairil, M.; Wan Juliana, W.A.; Nizam, M.S.; Razi Idris, W.M. (Universiti Kebangsaan Malaysia, 2014)
Three forest types were recognized at Chini watershed namely inland, seasonal flood and riverine forests. The soil physico-chemical characteristics from the three forest types were investigated to determine the soil properties variation within a landscape scale. Thirty sampling stations were established, represented by fourteen inland, nine stations in seasonal flood forest and seven in riverine forest. In each station, three soil samples were taken at 0-15 cm depth by using an auger. The study showed 71% of the soil in the inland forest was found to be dominated by clay, 44% of the soil in the seasonal flood forest by clay loam and 42% of the soil in the riverine forest was dominated by silty clay. The pH of all three types of forest studied was acidic and insignificantly different. Organic matter content in the study sites was moderate. The mean of electric conductivity (EC) and cation exchange capacity (CEC) values in the studied soils were low. Based on ANOVA, there were significant differences of the available P and K, K+, Ca2+ and Mg2+ cations and electrical conductivity amongst the three forest types (p< 0.05). Cluster analysis showed that the variations of the soil physico-chemical characteristics between the three forest types were low thus indicating that the soil physico-chemical investigated in this study were not the only main contributing factors in floristic variation of the three forest types in Chini watershed.